E-learning in Chinese higher education: the view from inside - McConnell, David (Springer, 2018)
Despite the upsurge in interest in e-learning (or online learning) in Chinese higher education, little is known about the ways in which lecturers design and run their online courses, or about how they perceive e-learning. This paper reports the results of interviews with higher education teachers in China working in conventional, campus-based universities, concerning their conceptions and beliefs of e-learning. The interviews were analysed from a grounded theory perspective that gave rise to seven emerging themes, namely: the ‘centrality of the lecture’, ‘online cooperative learning’, ‘network learning’, ‘student learning’, ‘lecture plus online work’, ‘infrastructure and access’ and ‘professional development’. Discussion of these emerging themes helps us understand the ways in which these teachers think about e-learning and teaching, the beliefs they hold about their ‘e’ practice, the ways in which they implement e-learning, the problems they face in incorporating e-learning into their courses and the ways in which they perceive e-learners. This provides a fascinating and unique insight into e-learning in Chinese higher education. Evidence shows that it is a complex area with many influences, some of which can be attributed to social, cultural and Confucian-heritage factors. It is concluded that, despite enthusiasm by some for innovating e-learning, the dominance of traditional teaching methods in China suggest that the conditions for mainstreaming e-learning in the near future are not strong.